Aspects of the reception of «Reformpädagogik» (progressive education) - Oelkers, Jürgen (Swiss Journal of Educational Research, 2019)
In standard historiography, «Reformpädagogik» (progressive education) is described as a separate historical epoch and understood as modernization that can be clearly distinguished. The article starts from a broader perspective and understands every pedagogy linguistically and mentally as «Reformpädagogik». Practical reforms of education and teaching are not necessarily tied to a particular pedagogy and the educational system develops out of itself. Therefore, the question of reception is complex and always includes phenomena that are ignored or strongly emphasized. Today, this again includes radical school criticism.